Liturgy's imagined past/s: methodologies and materials in the writing of liturgical history today - Berger, Teresa; Spinks, Bryan D. (A Pueblo book, 2016)
This book calls attention to the importance of scholarly reflection on the writing of liturgical history. The essays not only probe the impact of important shifts in historiography but also present new scholarship that promises to reconfigure some of the established images of liturgy’s past. Based on papers presented at the 2014 Yale Institute of Sacred Music Liturgy Conference, Liturgy’s Imagined Past/s seeks to invigorate discussion of methodologies and materials in contemporary writings on liturgy’s pasts and to resource such writing at a point in time when formidable questions are being posed about the way in which historians construct the object of their inquiry